2011
DOI: 10.1002/jbm.a.33204
|View full text |Cite
|
Sign up to set email alerts
|

Alignment and composition of laminin–polycaprolactone nanofiber blends enhance peripheral nerve regeneration

Abstract: Peripheral nerve transection occurs commonly in traumatic injury, causing deficits distal to the injury site. Conduits for repair currently on the market are hollow tubes; however, they often fail due to slow regeneration over long gaps. To facilitate increased regeneration speed and functional recovery, the ideal conduit should provide biochemically relevant signals and physical guidance cues, thus playing an active role in regeneration. To that end, laminin and laminin–polycaprolactone (PCL) blend nanofibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 33 publications
2
106
0
1
Order By: Relevance
“…The peaks characteristic of laminin was nearly invisible in the spectra produced from PLCL/Lam(B) and PLCL/Lam(CS) nanofibers, where we concluded that the amount of laminin incorporated in PLCL solution was probably too low [PLCL:laminin 1600:1] and thus the concentration of protein on the surfaces of the scaffold was below the determination capability of the equipment. Studies of PCL-laminin blended nanofibers carried out by Neal et al also utilized Fouriertransform infrared spectra where they demonstrated that the peaks representing amide bonds (1564 cm À1 , 1649 -cm À1 ) from laminin are very small for fibers with 0.1 wt% concentration of laminin [34] and the concentration of the protein in PLCL/Lam(B) was much lower with a value of about 0.006 wt%. On the other hand, the application of core-shell nanofibers was quite advantageous since laminin remains encapsulated within the core of the fiber and was not detected on the surface of the fibers, allowing suitable encapsulation of the bioactive factors.…”
Section: Morphology Chemical and Mechanical Properties Of The Scaffoldsmentioning
confidence: 96%
“…The peaks characteristic of laminin was nearly invisible in the spectra produced from PLCL/Lam(B) and PLCL/Lam(CS) nanofibers, where we concluded that the amount of laminin incorporated in PLCL solution was probably too low [PLCL:laminin 1600:1] and thus the concentration of protein on the surfaces of the scaffold was below the determination capability of the equipment. Studies of PCL-laminin blended nanofibers carried out by Neal et al also utilized Fouriertransform infrared spectra where they demonstrated that the peaks representing amide bonds (1564 cm À1 , 1649 -cm À1 ) from laminin are very small for fibers with 0.1 wt% concentration of laminin [34] and the concentration of the protein in PLCL/Lam(B) was much lower with a value of about 0.006 wt%. On the other hand, the application of core-shell nanofibers was quite advantageous since laminin remains encapsulated within the core of the fiber and was not detected on the surface of the fibers, allowing suitable encapsulation of the bioactive factors.…”
Section: Morphology Chemical and Mechanical Properties Of The Scaffoldsmentioning
confidence: 96%
“…To avoid these surface modifications, some researchers have blended natural polymers and other bioactive molecules with the synthetic polymer solution prior to the electrospinning thus specifically functionalizing the nanofibers for particular TE applications. Collagen, laminin, gelatin, elastin and chitosan have extensively been blended with synthetic polymers to produce nanofibers serving as scaffolds for nerve, blood vessels, skin and bone regeneration together with other TE applications [98][99][100][101][102][103]. Carbon phosphates, serving as bone grafting replacements to fill bone empty spaces and damaged areas, have been blended with polymer solutions to fabricate nanofibers having potentials in osteoconductivity, osteoinductivity and osteointegration [104][105][106].…”
Section: Different Functionalization Approaches Of Electrospun Biodegmentioning
confidence: 99%
“…Coating of peripheral nerve conduits can enhance nerve regeneration process and solve longer nerve gaps repair. Resource to extracellular matrix materials, such as fibronectin, laminin and collagen, give naturally hydrophobic scaffolds a hydrophilic surface that promotes cell adhesion [73,116,174]. Collagen Type I conduits coated with laminin and fibronectin have shown improved neural regeneration [175,176].…”
Section: Conduits Structure Modulationmentioning
confidence: 99%